Repositioning of fluoroquinolones from antibiotic to anti-cancer agents: An underestimated truth - Vikas Yadav (Biomedicine & Pharmacotherapy, 2019)
Increasing development costs and higher failure rate in clinical trials has reduced the repertoire of newer drugs in the market for clinical use. The most appropriate approach to end the search for newer drugs is “Repositioning”, as it requires less time and money to explore new indication of existing drug or failed drug. In the past, several drugs have been repositioned for different indication but the full potential remains unharnessed. With rise in cancer prevalence and treatment costs, it is imperative to search for newer drugs and the use of repositioning approach may help us. Fluoroquinolones has been used as antibiotics for over four decades now, but recent research highlighted their use as pharmacological compounds with multifaceted implication. Repositioning of fluoroquinolones into anti-cancer molecule seems to be a highly plausible option owing to their profound immunomodulatory, pro-apoptotic, anti-proliferative and anti-metastatic potential. The present review provides a comprehensive account of the recent and past explorations pertaining to the anti-cancer activity of fluoroquinolones and also discusses the various approaches that are being considered to remodel them for the treatment of cancer.